Tinjauan Yuridis Terhadap Putusan Hakim Dalam Kasus Tindak Pidana Penganiayaan Berat (Studi Kasus Putusan No. 568/Pid.B/2014/PN.Jak.Sel) - Andi Kurniawan; Tardip Panggabean; Riana Wulandari Ananto (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
Cases of serious maltreatment are one of the legal problems that have a serious impact on victims and society in general. The handling of such cases requires a careful review of the judge's decision to ensure justice and appropriate legal protection. This research aims to juridically analyze the judge's decision in a case of serious maltreatment, by taking a case study of Decision No. 568/Pid.B/2014/PN.Jak.Sel. The approach method used is normative juridical research method with data collection through literature study. The results of the analysis show that the judge's decision has considered various factors such as existing evidence, applicable law, and the principles of criminal law. However, there are several aspects that require further attention, such as consideration of the punishment imposed in proportion to the crime committed and consideration of rehabilitation of the perpetrator. Therefore, wisdom is needed in law enforcement as well as a deep understanding of the value of justice in court decisions.